Health-Related Quality of Life in Bariatric and Metabolic Surgery - Coulman, Karen D. (Curr Obes Rep, 2020)
PURPOSE OF REVIEW: This review describes the latest evidence for the impact of bariatric surgery on health-related quality of life (HRQL). RECENT FINDINGS: The impact of bariatric surgery on HRQL is less well-understood than its clinical effectiveness on weight and co-morbidities. Poor-quality study design and different HRQL measures challenge systematic reviews and meta-analyses. Available limited evidence suggests that physical aspects of HRQL may improve more than mental health aspects of HRQL after bariatric surgery, reaching maximal benefits 1–2 years post-surgery. Comparative HRQL analyses between bariatric procedures cannot be made due to a lack of randomised data. Qualitative research highlights the tensions patients experience after bariatric surgery, which provides insights to observed changes in HRQL. SUMMARY: Standardized HRQL measures are being developed and agreed to improve future evidence synthesis. Two multi-centre randomised trials of bariatric surgical procedures including detailed HRQL assessment are in progress. It is hoped that the combination of comparative high-quality HRQL data and information from qualitative studies will provide new insights into patient well-being and health after bariatric surgery.